A new world of terror. - Zorpette, G. (IEEE spectrum)
At first glance, at least, it seems the array of counter terrorism technologies under development in the United States and elsewhere would have been useless to prevent the 11 September attacks. Neither airport detectors that can sense plastic weapons and explosives nor state-of-the-art sensors that could ferret out the chemicals, biological agents, or nuclear materials of mass destruction would have revealed the presence of murderous fanatics armed with box-cutters. And if the deed was the work of terrorist networks that operated with minimal electronic communications among cells, there would have been little opportunity for technical methods, such as signals intelligence, to unmask the plot. After years in which technology appeared likely to make serious inroads into international terrorism, a new reality has dawned, one in which the enemy has proved far more sophisticated, determined, adaptable, and resourceful than was previously imagined. Nevertheless, that revelation does not suggest it is time to abandon or even curtail work on technical aspects of counterterrorism, some analysts say. Rather, it is time to review technical methods and intelligence as part of what must necessarily become a far larger tool box. Following the attack, it has been suggested that the emergency planners and city officials need a new strategy now that the enemy ?has our playbook?. Part of the terrorists' playbook is to inflict as much damage as possible, including maximum carnage among rescue teams. The new strategy should be to think like the terrorists